Ferramenta para análise do desempenho acadêmico, utilizando como caso de teste o período sob influência do covid-19 - Queiroz, Leonardo Junio Alves de (2022)
The academic performance of students at the Universidade Federal do Rio Grande do Norte (UFRN) throughout the semesters is important information to measure the quality of teaching and the socioeconomic impact, becoming even more important in times of pandemic. With the emergence of the Covid-19, a disease caused by the coronavirus agent identified in December 2019 in China, where it expanded to all other countries, proved an even more important tool to analyze performance and influence of factors external in the academic regime. Given this, the objective of this work was to propose a tool for the study of student performance, using the Anaconda Software with Python programming language and concepts in the area of data science, from data collection to interpretation and analysis of the data and considering the pandemic periods as a test case, verifying student success in academic disciplines between semesters, considering the statuses regarding approvals, disapprovals, locked and dropouts, in addition to socioeconomic data and a mockup. With this, show the importance of this tool, being able to contribute a lot to the teaching in the university helping students and professors, in addition to analyzing the impact caused by Covid-19 in education.